A Rare Differential Diagnosis of a Solitary Anterior Neck Mass - Saniasiaya, Jeyasakthy; Mohamad, Irfan (Oman Medical Specialty Board, 2016)
Patients with anterior neck masses commonly present to otorhinolaryngology clinics, but there are limited differential diagnoses for such lesions. Common ones include thyroid nodule and thyroglossal duct cyst. In an elderly patient, a differentiated thyroid carcinoma should be suspected especially if it moves with swallowing. We encountered a typical presentation of a solitary thyroid nodule-like mass with the exception of pulsation in a 65-year-old female. Further investigation, using neck ultrasonography, revealed that it was a variant of right common carotid artery arising from the left common carotid artery. Knowledge of such variants is of great importance as ignorance of such a variation may lead to inadvertent surgical complications during procedures.